Agglomeration and Regional Unemployment Disparities A Theoretical Analysis with Reference to the European Union - Südekum, Jens (cege-Schriften, 2018)
In the European Union, unemployment rates differ markedly across regions, both within and across nations. This study presents a coherent theoretical approach to explain the emergence and persistence of such regional unemployment disparities. The analysis builds on the wage curve literature, and on regional agglomeration theories like the new economic geography. These theoretical strings are combined and extended, in order to provide a unified framework.